Reformulasi Mekanisme Pengangkatan Pejabat Kepala Daerah sebagai Upaya Penguat Sistem Demokrasi - Fajri, Pujangga Candrawijayaning (IAIN Metro, 2023)
Indonesia is a unitary state that adopts a system of regional autonomy in terms of the maintenance of its country, which has the consequences of the existence of official Heads of District in each region. The head of the district is democratically elected every five years through an electoral mechanism. However, with the 2024 simultaneous elections being held, there is a vacancy in the office of the head of district due to the expiration of the term of the previous head of area, so the mechanism used to fill the vacancies is the appointment of the District Chief Officer who will be appointed on Permendagri No. 4 of 2023. It raises legal issues because Permendagri a quo is deemed to harm the notion of democracy by amputating the rights of the people to participating in the decision-making of the District Chief. The study aims to provide a contribution to the thinking of reformulating the mechanism of appointment of the District Chief in order to run more democratically. So this kind of research is normative jurisprudence using a legislative approach, a conceptual approach, and a case approach by relying on the legal material of the library. The result of this study is that given that the District Chief Officer is a strategic position and given that Indonesia is a democratic state, there is a need for a mechanism for the appointment of the District Head Officer based on the principles of openness in the process, transparency of information, and the presence of public participation, which is practically carried out by: (1) announcing the names of the candidates for the Regional Chief of Staff proposed by the Councillor and Governor. (2) The DPRD which is the regional legislative body should absorb the aspirations of the public through public hearings so that the criteria for the candidate for the District chief of staff to be proposed are in accordance with the needs of the region. (3) conducting a public test so that each proposed District Chiefs of Staff candidate knows his capacity before finally being determined by a final assessment team to become a District Head of Staff.